Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic